Nematodes (Mermithidae) parasitizing grasshoppers (Orthoptera: Acrididae) in the Pampean region, Argentina - Rusconi, José Matías (2017)
This work provides the results of a survey of entomonematodes parasites of grasshoppers in grasslands of the Pampean Region, Argentina. Nymphs of Staurorhectus longicornis Giglio-Tos, Laplatacris dispar Rhen, 1939, Dichroplus elongatus Giglio-Tos, 1894 and Metaleptea brevicornis (L.) (Orthoptera: Acrididae) were collected. Mermithidae was the only family registered with seven species: Agamermis decaudata Cobb, Steiner and Christie, 1923, Amphimermis bonaerensis Miralles and Camino, 1983, Amphimermis dichroplusi Camino and Lange, 1997, Amphimermis ronderosi Camino and Lange, 1997, Hexamermis coclhearius Stock and Camino, 1992, Hexamermis ovistriata Stock and Camino, 1992, and Longimermis acridophila Camino and Stock, 1989. The values of parasitism ranged between 1-12%, and intensity not overcome the number of 5.0 nematodes per larva. The nematodes observed showed specificity, not registering the same species of parasite in more than one host species. The Pampean region constituted an area with high diversity of mermithids where new species could be consider as bioregulator agents of this troublesome insect pests in agricultural areas of Argentina.